Grain-filling of superior spikelets and inferior spikelets for japonica rice under low-amplitude warming regime in lower reaches of Yangtze River Basin. (5th January 2021) - Dou, Zhi; Zhang, Haixiang; Chen, Wenzhu; Li, Ganghua; Liu, Zhenghui; Ding, Chengqiang; Chen, Lin; Wang, Shaohua; Ding, Yanfeng; Tang, She
Abstract: Grain-filling, as the final growth stage of rice, is sensitive to environmental temperature change. Previous studies mainly concerned about the effects of high temperature stress during grain-filling on rice growth, and most experiments were carried out with pot for cultivating rice and greenhouse for warming. This research investigated the response of rice grain-filling of superior spikelets (SS) and inferior spikelets (IS) of two japonica cultivars to elevated temperature during grain-filling stage under open-field warming conditions in lower reaches of Yangtze River Basin using free-air temperature enhancement facility. Results indicated that rice yield was not significantly changed by warming less than 4°C. SS and IS showed different responses to elevated temperature during the grain-filling stage, whereas there were similar trends between two cultivars and years. For SS, although elevated temperature enhanced its filling rate during the early grain-filling period, and caused a shorter grain-filling period and a lighter grain weight; for IS, elevated temperature improved its grain weight by enhancing its filling rate during middle and late grain-filling period due to the increased number of days with suitable temperature. For both SS and IS, key starch biosynthesis enzymes and indole-3-acetic acid content exhibited generally a similar dynamics trend with grain-filling rates, and these sink strength parameters presented higher levels under elevated temperature relative to natural temperature for IS during middle and late grain-filling period. Consequently, warming less than 4°C presented different influences on SS and IS; the improvement of IS filling under warming regime was associated with the intensification of grain sink strength.